Linguocultural Features of National Costume Names in Uzbek and English Languages: A Comparative Study - Farogat Normurodova (Athena: Journal of Social, Culture and Society, 2026)
transmitting cultural heritage. National costume terminology reflects not only lexical meanings but also the historical development, cultural identity, social values, and worldview of a particular nation. This study investigates the linguocultural characteristics of national costume names in Uzbek and English through a comparative linguistic and cultural analysis. The research examines semantic structures, etymological origins, symbolic meanings, and cultural connotations associated with traditional clothing terminology in both languages. A qualitative comparative methodology was employed using descriptive, semantic, etymological, and linguocultural approaches. Lexical units such as chapan, doppi, atlas, adras, paranja, and belbog' in Uzbek were compared with English cultural equivalents including cloak, robe, bonnet, veil, shawl, and waistcoat. The findings reveal that Uzbek costume terminology is deeply connected with ethnic traditions, family values, social hierarchy, craftsmanship, and ceremonial customs, whereas English costume vocabulary reflects historical evolution, class distinctions, regional identities, and Western cultural transformations. Although certain lexical items possess functional equivalence, many concepts remain culturally specific and require explanatory translation because of their unique ethnocultural significance. The study demonstrates that national costume terminology represents an essential component of cultural memory and linguistic identity. The results contribute to comparative linguistics, ethnolinguistics, intercultural communication, translation studies, and cultural heritage research.